PEMBELAJARAN MELALUI PEMECAHAN MASALAH UNTUK MENCAPAI KETUNTASAN BELAJAR KELILING DAN LUAS DAERAH LINGKARAN SISWA SMP - Sri Rahayuningsih (Universitas Brawijaya, 2014)
Problem solving is an important aspect of learning mathematics. The fact indicates that the learning outcomes of students in perimeter and area of the circle is low. Therefore, we need a serious effort to help student master perimeter and area of the circle through problem solving instruction. The aims of this study are to describe: 1) the design of mathematics instruction through problem solving approach to achieve student mastery in perimeter and area of the circle, 2) the student achievement in perimeter and area of the circle through this instruction, and 3) students respond toward this instruction. This study used a qualitative approach and classroom action research design. The subject of this study is eighth grade students in SMP Kartika IV-9 Malang. The result shows that the instruction can achieve mastery learning in perimeter and area of the circle and the students respond is very positive toward this instruction. Therefore, it is suggested to the teachers to apply this instruction in their teaching.